Centralised, energy positive wastewater treatment shows high potential for carbon neutrality with emissions offset through biogas and biosolids use - Isabel Schestak; A. Prysor Williams (Journal of Water Process Engineering, 2025)

Responding to the UN sustainability goals in transdisciplinary partnership through network action learning - Katrin Dreyer-Gibney; Paul Coughlan; David Coghlan; Szu-Hsin Wu; Aisha Bello-Dambatta; Richard Dallison; Aonghus McNabola; Daniele Novara; Annum Rafique; Isabel Schestak; Jan Spriet; Nathan Walker; et al. (Environment, Development and Sustainability, 2024)
The global water crisis, an enormous concern according to the World Economic Forum, poses a significant challenge to long-term sustainability, exacerbated by the high energy demand associated with water supply and treatment. As the renewable energy sector grows, the need for green technologies to support the water-energy nexus becomes evident. However, mere technological advancements are insufficient to address complex water-related challenges. This paper presents a transdisciplinary collaborative effort involving engineers, geographers, management researchers, and environmentalists working with practitioners in a cross-border network. The study explores through action learning research how, in a transdisciplinary partnership, network action learning influences the exploration and implementation of novel green technology and the development of innovation capabilities. The research is structured around three themes: green technology platforms, policy support and guidance, and dissemination and collaboration. It identifies the factors impacting technology exploration and application and how concurrently green innovation capabilities are developed. The study emphasizes the significance of transdisciplinary collaboration and offers valuable insights into addressing UN Sustainability Goals related to clean water, sustainable industry, and partnerships. It contributes to innovation capability theory and provides practical guidance to researchers, practitioners, and policymakers, emphasizing the need for holistic approaches to address the water-energy crisis and achieve sustainable development.

Optimising sustainability: Circular pathways for Scotch Whisky distillery co-products - Colm Duffy; David Styles; Isabel Schestak; Kenneth Macgregor; Frances Jack; Daniel Henn; Kirsty Black; Pietro P.M. Iannetta (Journal of Cleaner Production, 2023)

Heat recovery and water reuse in micro-distilleries improves eco-efficiency of alcohol production - Isabel Schestak; Jan Spriet; Kirsty Black; David Styles; Maria Faragò; Martin Rygaard; A. Prysor Williams (Journal of Environmental Management, 2023)